Corrosion properties of the skin of high pressure die cast AZ91 alloy - C. Blawert (Canadian Institute of Mining, Metallurgy and Petroleum, 2005)
In previous studies of various HPDC magnesium alloys we found that the corrosion properties of the skin are inferior in comparison to the bulk, However, this is surprising as one would expect better corrosion properties for the finer microstructure of the skin, In a more detailed study using 2 and 6 mm thick sections from HPDC AZ91 step plates, the corrosion results of the original skin, the slightly removed skin and the bulk were compared, Indeed, the corrosion measurements including potentiodynamic polarization, long term polarization resistance measurements and electrochemical impedance spectroscopy (EIS) revealed a lower corrosion resistance of the original as-cast skin. An explanation for this corrosion behavior was found, on the one hand, in the microstructure concerning especially the amount and distribution of the 13-phase and, on the other hand, in the composition, including the distribution of the most important alloying element Al and of some impurities such as Fe.